High Production of Soluble Iron Promoted by Aerosol Acidification in Fog. Issue 12 (23rd June 2020) - Shi, Jinhui; Guan, Yang; Ito, Akinori; Gao, Huiwang; Yao, Xiaohong; Baker, Alex R.; Zhang, Daizhou
Abstract: The current poor understanding of soluble iron (Fe) yield in atmospheric aerosols leaves two observational facts having not yet been correctly simulated in numerical models: the high Fe solubility in aerosols with low Fe content and, hence, the wide range of observed Fe solubility. Our observation at Qingdao, a coastal city of China, revealed that soluble Fe was produced along with aerosol acidification much more efficiently in fog than under other weather conditions. The median Fe solubility in fog aerosols, 5.81%, was 3.3 times of that in haze aerosols, 5.2 times of that in clear days, and 21.5 times of that in dust aerosols. Involving fog processing in models may reduce the discrepancy in the atmospheric flux of soluble Fe to the ocean between numerical simulations and field observations. Plain Language Summary: Aerosol soluble Fe depositing into seawater promotes marine primary productivity, alters global ocean carbon storage, and ultimately affects global climate. Current models largely underestimate the concentration of soluble Fe in aerosols, but the reason is not clear. Our present results revealed the high efficiency of fog to drive the conversion of Fe from insoluble form to soluble form in the atmosphere, a process that has been overlooked in models. To increase the simulation accuracy, proper inclusion of fog processing in models is necessary. Key Points: Conversion of aerosol Fe from insoluble form to soluble form in fog was much more efficient than in haze and dust Underestimation of aerosol soluble Fe in latest models was largely caused by inaccurate simulation under fog conditions Proper description of processing of aerosol Fe in fog in models is essential to improve simulations